SALUD Y CRECIMIENTO ECONÓMICO: INFLUENCIAS TEÓRICAS Y VINCULACIONES EMPÍRICAS - Monterubbianesi, Pablo Daniel (Universidad de Costa Rica, 2014)
The aim of this article is to describe the main channels of influence of health status oneconomic growth. Also, to conduct a comparative statistical analysis on the situationbetween the different countries and regions about health and income. Finally, attempt toverify from the empirical point of view, using clustering technique in installments, theexistence of a close relationship these dimensions, considering the relative situation ofdifferent countries.